Commuting in the Baltic States: Patterns, determinants and gains - Mihails Hazans (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
To what extent does commuting reduce urban – rural and regional wage disparities? This question is addressed by estimating two sets of earnings functions (based on 2000 LFS data for Estonia, Latvia and Lithuania): with location variables (like capital city, rural etc.) measured at the workplace and at the place of residence. The main finding is that in Estonia and Latvia commuting has significantly narrowed the ceteris paribus wage gap between capital city and rural areas, as well as between capital and other cities. In Lithuania only residents of urban areas in the capital county manage to catch up significantly with the capital, while overall urban-rural gap remains almost unchanged. So different outcomes are explained by country-specific skills composition of rural – urban commuting flows and wage discrimination against rural residents in Lithuanian urban markets. Individual gains to rural – urban or inter-city commuting (both with and without correcting to selectivity) are uniformly big in Latvia but on average negligible in Lithuanian urban areas.
Keywords: J31; J61; R23; D63; C31; C35; 330; commuting; earnings functions; treatment effects model; wage disparities; Baltic States; ethnic minority